Understanding embryonic development for cell‐based therapies of intervertebral disc degeneration: Toward an effort to treat disc degeneration subphenotypes. Issue 3 (14th July 2020) - Tessier, Steven; Risbud, Makarand V.
Abstract: Chronic low back and neck pain are associated with intervertebral disc degeneration and are major contributors to the global burden of disability. New evidence now suggests that disc degeneration comprises a spectrum of subphenotypes influenced by genetic background, age, and environmental factors, which may be contributing to the mixed outcomes seen in clinical trials of cell‐based therapies that aim to treat disc degeneration. This problem is further compounded by the fact that disc degeneration and aging coincide with an exhaustion of endogenous progenitor cells, imposing limitations on the regenerative capacity of the disc. At the bench‐side, current work is focused on applying our knowledge of embryonic disc development to direct and refine differentiation of adult and human‐induced pluripotent stem cells into notochord‐like and nucleus pulposus‐like cells for use in novel cell‐based therapies. Accordingly, this review presents the salient features of intervertebral disc development, post‐natal maintenance, and regeneration, with emphasis on recent advancements. We also discuss how a stratified approach can be undertaken for the development of future cell‐based therapies to bring emerging subphenotypes into consideration. Key Findings: Intervertebral disc disease is an umbrella term that encompasses a spectrum of degenerative conditions; this notion may be an impeding factor for the success of cell-based therapies. Current research is focused on applying our knowledge of embryonic disc development to direct human‐induced pluripotent stem cells into notochord‐like and nucleus pulposus‐like cells for use in novel cell‐based therapies to optimize treatment. Designing cell‐based therapies that target specific disc degeneration subphenotypes may be a way forward to better address these complex and painful conditions.